Pendampingan Teknis Pembuatan Mesin Tetas Ekonomis melalui Pengabdian kepada Masyarakat Teritegrasi KKN-Tematik di Kecamatan Nambo Kota Kendari - Abadi, Musram; Nafiu, La Ode; Saili, Takdir; Libriani, Restu; Sulfitrana, Andini; Salido, Wa Laili; Isnaeni, Purnaning Dhian (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2020)
The COVID-19 pandemic is a health crisis that is affecting almost all parts of the world community. The corona virus affects not only the health sector but also other sectors such as education, social affairs, culture, religion and the economy. The livestock industry, especially poultry, also felt the effects. One of the areas affected by COVID-19 is the Nambo District in Kendari City. Farmers find it difficult to get local DOC chickens because the breeding company limits DOC production. The economic innovation in slip machine technology is an alternative problem solving for the procurement of DOC. The FPt UHO Thematic KKN program, through the technical support of local chicken breeders through the introduction of innovative economic incubator technology, is expected to overcome the problems of people losing their source of income while maintaining the COVID-19 protocol. This activity program will run from June 13, 2020 to July 13, 2020 for one month in the Nambo District of Kendari City. The program is implemented in the form of Technical Guidance and Counseling, whereby the Covid 19 prevention protocol is still observed. The results of the KKN Tematik FPt UHO program, namely to improve the knowledge and skills of farmers by applying simple technological innovations through technical guidance to produce economical incubators that can reduce the cost of purchasing DOC increase farmers' income during the COVID-19 pandemic